Needs Analysis of Arabic Guided Writing Material Using Task-Based Learning - Hakim, Muhammad Kamal bin Abdul (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
Writing is not only as academic skills but also it as as important skills to facilitate the career and life needs. Writing material must be designed to realize the skills that are directly implemented in daily life. Therefore, the needs analysis process is a necessity to find out those needs. The aim of study was to get the students’ needs of Arabic guided writing material through task-based learning. Writing has to create as task learning because it needs more practice. This study needs to design guided material. The research used qualitative research using descriptive qualitative method. The process of collecting data used documentation, interview and questionnaire. Data analysis used descriptive qualitative technique and judgment experts. The result of finding show that teacher and students need authentic material refers to practice. Task-based learning has offered the variation of task. Almost the participant answered that the types of task is available with the Arabic guided writing learning. This study is not oriented to the writing material content but also combined with the variation task activity. It can be implemented in guided writing subject. The consortium is able to develop in the material arranging.